2014
DOI: 10.3168/jds.2013-7365
|View full text |Cite
|
Sign up to set email alerts
|

Use of just-about-right scales and penalty analysis to determine appropriate concentrations of stevia sweeteners for vanilla yogurt

Abstract: With the mainstream emergence of natural sweeteners such as stevia, which is available in different commercial formulations, suitability for yogurt needs to be validated. The present study aimed to determine the appropriate concentration level of 3 processed stevia sweeteners/supplements in commercial plain low-fat yogurt flavored with natural vanilla. Three different levels of sucrose, aspartame, an erythritol and 95% rebaudiana A stevia sweetener, a 95% pure mix of maltodextrin and steviol glycosides, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 25 publications
0
43
1
1
Order By: Relevance
“…A few studies have used penalty analysis in a dairy foods consumer study: in cottage cheese (Drake et al, 2011) and in vanilla yogurt with stevia (Narayanan et al, 2014).…”
Section: Overview Of Sensometric Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have used penalty analysis in a dairy foods consumer study: in cottage cheese (Drake et al, 2011) and in vanilla yogurt with stevia (Narayanan et al, 2014).…”
Section: Overview Of Sensometric Techniquesmentioning
confidence: 99%
“…Furthermore, a sensitivity analysis was performed to provide a measure of the relative importance among the inputs of the neural network model and to illustrate the model output variability as a function of the change in the input variable. The JAR scores were evaluated through penalty analysis, being considered significant when more than 20% of consumers evaluated the sample above or below JAR (Drake et al, 2011;Narayanan et al, 2014). The purchase intent data, computed in binomial form (1, representing buy, >3; 0, representing not buy, ≤3), were correlated with data from the JAR scale and acceptance test by LR to find the affective characteristics that most influenced the purchase intent of the product (Cruz et al, 2011).…”
Section: Tn Tp Tn Tp Fn Fpmentioning
confidence: 99%
“…Zhang and Gruen () determined the iso‐sweetness of natural sweeteners rebaudioside A, monk fruit, erythritol, lactitol, and xylitol to 10.1% sucrose sweetened whey protein beverages and reported that rebaudioside A had the highest sweet taste potency followed by monk fruit extract (77 to 115 times sweet as 10.1% sucrose), whereas erythritol, lactitol, and xylitol were less sweet than sucrose. Narayanan and others () determined that the appropriate concentrations of stevia sweeteners for naturally flavored vanilla low fat yogurt were intermediate levels (0.7 to 5.5%, wt/wt). Morais and others () compared stevia with other artificial sweeteners in chocolate dairy desserts and reported that stevia was the weakest sweetener followed by aspartame, sucralose, and neotame was the strongest.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the past years several publications reported successful results using JAR scales, for example, for development of fruit filling (Agudelo and others ), nutraceutical‐rich juices (Lawless and others ), and aleurone‐rich pastas and breads (Bagdi and others , ). JAR scales are also widely used to develop dairy products, for example sweetener concentrations in vanilla yoghurts (Narayanan and others ), chocolate dairy desserts (Morais and others ), inulin fortified ovine milk yoghurt (Balthazar and others ), and coffee‐flavored milk (Li and others ). The improvement of OAL during product development processes strongly depends on the initial OAL of the products.…”
Section: Introductionmentioning
confidence: 99%